The barley lectin carboxyl-terminal propeptide is a vacuolar protein sorting determinant in plants. - Bednarek, S Y (1991)
We have previously shown that the 15-amino acid carboxyl-terminal propeptide of probarley lectin is necessary for the proper sorting of this protein to the plant vacuole. A mutant form of the protein lacking the carboxyl-terminal propeptide is secreted. To test whether the carboxyl-terminal propeptide is the vacuole sorting determinant of probarley lectin, we examined in transgenic tobacco the processing and sorting of a series of fusion proteins containing the secreted protein, cucumber chitinase, and regions of probarley lectin. Pulse-labeling experiments demonstrated that the fusion proteins were properly translocated through the tobacco secretory system and that cucumber chitinase and cucumber chitinase fusion proteins lacking the carboxyl-terminal propeptide were secreted. The cucumber chitinase fusion protein containing the carboxyl-terminal propeptide was properly processed and sorted to the vacuole in transgenic tobacco as confirmed by organelle fractionation and electron microscopy immunocytochemistry. Therefore, the barley lectin carboxyl-terminal propeptide is both necessary and sufficient for protein sorting to the plant vacuole.